Utilización de plantas medicinales como sustituto de antibióticos en producción de pollos de engorde - Ortíz Saquicaray, Verónica Tatiana (2011)
The present thesis was carried out in the facilities of the Experimental Farm "Santa Inés" of the Technical University of Machala, located in the road Machala-passage. The objectives of this investigation were: To determine the gain of weight, nutritious consumption and nutritious conversion. To determine the effectiveness of each one of the treatments from the productive point of view and to Know the mortality and production costs. With a duration of six weeks, 225 chickens were used prepared in three treatments with three repetitions of fifteen chickens each one. Concluded this time, you reached the following conclusions: The gain of weight was significant with the consumption of medicinal plants, charge everything with the Pepper. The consumption of food of the birds with the incorporation of the extracts provides a better increment of weight. The appropriate use of the medicinal plants in the daily feeding of the chickens allows that these have a bigger food consumption during its development. The nutritious conversion was expressed inside the expectations for each one of the treatments applied with extracts of medicinal plants. The utilities were equal for the five treatments, ($42,00). The flavor of the meat doesn't present any variation or alteration.